The Functions of The Gate of Wali Loram Kulon Mosque in Kudus Regency - Ikram, Fadhli Dzil; Syakir, Syakir; Ibnan Syarif, Moh. (Catharsis, 2021)
One of the architectural relics in Kudus beside the Menara Kudus Mosque, there is the Gate of Wali Loram Kulon Mosque. The gate implicitly functions as a religious, social and cultural center for the Loram community. This study aims to describe the function of Wali Mosque gate for the Loram Kulon community in Kudus Regency. This research studied the individual functions, social functions and physical functions. This study used descriptive qualitative method. Meanwhile, data analysis used observation, interviews and documentation. The results of this study indicate that the Loram Kulon community around Wali Loram Mosque is a religious community. It was proven by the belief in carrying out the Shari'a, traditions and customs as well as social and cultural life. Harmony and tolerance are the results of the gate function. There are three traditions that exist and lead to the gate of Wali Loram Kulon Mosque in Kudus. They are Sego Kepel or rice ball tradition, Nganten Mubeng Gapuro, and Ampyang Maulid tradition. People believe that bad things will happen if they do not carry out the traditions. Therefore, the inheritance of cultural values can certainly be structured and transmitted at least through the local schools in Loram Kulon village, Kudus Regency to convey the local wisdom continuously.